A highly selective, sensitive and reversible fluorescence chemosensor for Zn2+ and its cell viability. Issue 9 (2nd February 2016) - Saini, Anoop Kumar; Srivastava, Mansi; Sharma, Vinay; Mishra, Veenu; Mobin, Shaikh M.
Abstract : A new ligand (H2 L ) was synthesized and designed for sensing properties.H2 L shows fluorescence ' switch ON ' with Zn 2+ ions with a detection limit of 1.47 μM. TheH2 L and1 showed marginal toxicity against MCF-7 and A375 cell lines. Abstract : A new imine conjugate Schiff base ligand (H2 L ) was prepared and evaluated for its sensing properties.H2 L detects Zn 2+ selectively among the wide range of metal ions. The sensing behavior ofH2 L was identified by UV-vis, fluorescence and 1 H NMR titration.H2 L shows fluorescence switch ON with the Zn 2+ ion among 18 other metal/heavy metal ions with a detection limit of 1.47 μM. The binding of Zn 2+ was confirmed by single crystal X-ray studies, which reveal the formation of binuclear complex (1 ). The packing diagram ofH2 L reveals the presence of rare linear C–H⋯C interactions (bond distance 2.79 Å and bond angle 180°) which form 1D-polymeric chains. Furthermore, the cytotoxicity ofH2 L and1 has been assessed against MCF-7 and A375 cell lines and both are found to have marginal toxicity.